Contribution of general practitioners and sexual health centres to sexually transmitted infection consultations in five Dutch regions using laboratory data of Chlamydia trachomatis testing. (May 2020) - Slurink, IAL; Groen, K; Gotz, HM; Meima, A; Kroone, MM; Hogewoning, AA; Ott, A; Niessen, W; Dukers-Muijers, NHTM; Hoebe, CJPA; Koedijk, FDH; Kampman, CJG; et al.
Effective sexually transmitted infection (STI) control requires opportunities for appropriate testing, counselling and treatment. In the Netherlands, people may attend general practitioners (GPs) and sexual health centres (SHCs; also known as STI clinics) for STI consultations. We assessed the contribution of GPs and SHCs to STI consultations in five Dutch regions with different urbanization levels, using data of urogenital Chlamydia trachomatis (CT) testing. Data (2011–2016) were retrieved from laboratories, aggregated by gender and age group (15–24 and 25–64 years). Results show that test rates and GP contribution varied widely between regions. GP contribution decreased over time in Amsterdam (60–48%), Twente (79–61%), Maastricht (60–50%) and Northeast-Netherlands (82–77%), but not in Rotterdam (65–67%). Decreases resulted from increases in SHC test rates and slight decreases in GP test rates. GPs performed more tests for women and those aged 25–64 years compared to SHCs (relative risks ranging from 1.49 to 4.76 and 1.58 to 7.43, respectively). The average yearly urogenital CT positivity rate was 9.2% at GPs and 10.7% at SHCs. Overall, GPs accounted for most STI consultations, yet SHC contribution increased. Continued focus on good quality STI care at GPs is essential, as increasing demands for care can not be entirely covered by SHCs.